Role of CXCR5+ CD8+ T cells in human immunodeficiency virus-1 infection - Gao, Leiqiong; Zhou, Jing; Ye, Lilin (Frontiers in Microbiology, 2022)
HIV infection can be effectively suppressed by lifelong administration of combination antiretroviral therapy (cART). However, viral rebound will occur upon stopping cART majority due to the long-term presence of an HIV reservoir, and it poses an ultimate barrier to drug-free virus remission. Memory CD4+ T cell subsets, especially TFH cells that reside in B-cell follicles within lymphoid tissues, are regarded as the predominant cellular compartment of the HIV reservoir. Substantial evidence confirmed that HIV-specific CD8+ T cells mediated cellular immunity can sustain long-term disease-free and transmission-free HIV control in elite controllers. However, mostly HIV cure strategies which look for expanded HIV-specific CD8+ T cells to control the virus are likely to fail largely due to the cellular exhaustion and TFH reservoir specialized anatomical structure that isolated largely HIV-specific CD8+ T cells entry into B-cell follicles. A loss of stem-like memory properties is a key feature of exhaustion. Recent studies found that CXCR5-expressed HIV-specific CD8+ T cells are memory-like CD8+ T cells and can migrate into B-cell follicles executes inhibition of viral replication. Moreover, this CD8 T-cell subset response to immune checkpoints blocking (ICB) treatment. In this Review, we discuss functions of this CD8 T-cell subset and propose the translation of these findings into viable HIV treatment and cure strategies.